Variety of genomic DNA patterns for nucleosome positioning - Ioshikhes, Ilya (Cold Spring Harbor Laboratory Press, 2011)
Precise positioning of nucleosomes along DNA is important for a variety of gene regulatory processes. Among the factors directing nucleosome positioning, the DNA sequence is highly important. Two main classes of nucleosome positioning sequence (NPS) patterns have previously been described. In the first class, AA, TT, and other WW dinucleotides (where W is A or T) tend to occur together (in-phase) in the major groove of DNA closest to the histone octamer surface, while SS dinucleotides (where S is G or C) are predominantly positioned in the major groove facing outward. In the second class, AA and TT are structurally separated (AA backbone near the histone octamer, and TT backbone further away), but grouped with other RR (where R is purine A or G) and YY (where Y is pyrimidine C or T) dinucleotides. As a result, the RR/YY pattern includes counter-phase AA/TT distributions. We describe here anti-NPS patterns, which are inverse to the conventional NPS patterns: WW runs inverse to SS, and RR inverse to YY. Evidence for the biological relevance of anti-NPS patterns is presented.